Magnetic seizure therapy in treatment-resistant depression: clinical, neuropsychological and metabolic effects. Issue 5 (25th November 2014) - Kayser, S.; Bewernick, B. H.; Matusch, A.; Hurlemann, R.; Soehle, M.; Schlaepfer, T. E.
Abstract : Background: Magnetic seizure therapy (MST), despite being in an early phase of clinical research, has been demonstrated to be associated with antidepressant efficacy. However, safety, tolerability and efficacy data in connection with functional brain activity from larger samples are lacking. The aim of this study was to determine clinical and cognitive effects of MST and the influence of MST on regional brain glucose metabolism. Method: Twenty-six patients suffering from treatment-resistant depression (TRD) underwent MST. Ten patients underwent a randomized trial and 16 patients an open-label study design. The primary outcome criterion was the severity of depressive symptoms assessed with the Hamilton Depression Rating Scale (HAMD). Depressive symptoms, tolerability and cognitive safety, along with social functioning and quality of life parameters, were assessed using various rating scales. A clinical follow-up visit 6 months following the completion of a course of MST and [ 18 F]-fluorodeoxyglucose positron emission tomography (FDG-PET) scans of 12 patients were analysed. Results: A significant response to MST was demonstrated by 69% of the patient sample, with 46% meeting remission criteria. Anxiety ratings were significantly reduced in responders and their quality of life was improved. Half of the responders relapsed within 6 months. No cognitive side-effects were observed. FDG-PET scans showed a metabolic increase in the frontal cortex bilaterally and a decrease in the left striatum. Conclusions: Robust antidepressant and anti-anxiety efficacy of MST was demonstrated, and found to be associated with localized metabolic changes in brain areas that are strongly implicated in depression. Thus, MST presents an effective, well-tolerated and safe treatment option for patients unable to respond to other forms of therapy for depression.